Neuromodulation techniques for enhancing lower extremity motor function in children with cerebral palsy (CP): a systematic review and meta-analysis of repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) interventions - Mansouri, Meysam; Amiri, Saba; Azizi, Shahla (Taylor & Francis Ltd, 2026)
PurposeTo evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) on gait and brain alteration in cerebral palsy (CP) children.Materials and methodsMEDLINE, Scopus, Google Scholar, Web of Science, and Cochrane were searched in February 2024 and updated in 9 October 2025. Randomized controlled trials (RCTs) with CP participants under 18, rTMS or tDCS intervention, and gait assessment were included. The risk of bias was assessed, and a meta-analysis was conducted using random-effect models.This review was registered in PROSPERO (ID: CRD42024555049).Results21 studies met the inclusion criteria. tDCS led to significant improvements in velocity (MD = 0.17, 95% CI = 0 to 0.35), gross motor function measure (GMFM), and functional independence. However, changes in other parameters such as step length, and cadence were not statistically significant and showed high heterogeneity. rTMS also improved overall motor function and walking performance in several studies, though data variability prevented meta-analysis. Both methods were safe and well-tolerated.ConclusionBoth interventions showed promise for improving velocity and GMFM in children with CP. However, due to inconsistent findings across other gait parameters and substantial heterogeneity, further large-scale, standardized RCTs with neuroimaging assessments are needed.
Keywords: Cerebral palsy; gait; rTMS; tDCS; neuromodulation